2018
DOI: 10.3389/fmats.2018.00004
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Molecular Simulations of Metal Organic Frameworks for CO2 Separation: Opportunities and Challenges

Abstract: Metal organic frameworks (MOFs) have emerged as great alternatives to traditional nanoporous materials for CO2 separation applications. MOFs are porous materials that are formed by self-assembly of transition metals and organic ligands. The most important advantage of MOFs over well-known porous materials is the possibility to generate multiple materials with varying structural properties and chemical functionalities by changing the combination of metal centers and organic linkers during the synthesis. This le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“… 14 , 15 We recently reviewed the large-scale simulation studies that aim to examine MOF adsorbents for CO 2 separations. 16 Watanabe and Sholl 17 performed grand canonical Monte Carlo (GCMC) simulations to calculate the adsorption isotherms of pure CO 2 and N 2 in 359 MOFs and presented ideal CO 2 /N 2 selectivities at infinite dilution. Haldoupis et al 18 studied 489 MOFs using GCMC simulations and reported ideal CO 2 /N 2 selectivities at infinite dilution, which was the biggest set of estimations for adsorption-based CO 2 /N 2 separation in MOFs at that time.…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 We recently reviewed the large-scale simulation studies that aim to examine MOF adsorbents for CO 2 separations. 16 Watanabe and Sholl 17 performed grand canonical Monte Carlo (GCMC) simulations to calculate the adsorption isotherms of pure CO 2 and N 2 in 359 MOFs and presented ideal CO 2 /N 2 selectivities at infinite dilution. Haldoupis et al 18 studied 489 MOFs using GCMC simulations and reported ideal CO 2 /N 2 selectivities at infinite dilution, which was the biggest set of estimations for adsorption-based CO 2 /N 2 separation in MOFs at that time.…”
Section: Introductionmentioning
confidence: 99%
“…Theinitial assessment for gas separation performances of MOFs is usually done using S ideal of MOFs in HTCS studies. [13,33] In Figure S7, we compared ideal CH 4 /H 2 selectivities of 1109 CFU-MOFs at infinite dilution, 1, 20, and 65 bar. Theh ighest differences are observed at infinite dilution.…”
Section: Effect Of Structural Discrepancies On Adsorbent Evaluation Mmentioning
confidence: 99%
“…Their functionalities can be well tuned by optimally selecting and/or changing the combination of metals and linkers, which provides them great potential as tunable materials for gas separations. Erucar and Keskin [49] summarized the fundamental steps for large-scale computational screening of MOFs (see Fig. 7).…”
Section: Porous Materials Screeningmentioning
confidence: 99%